Prostate Cancer Prevention by Silibinin - Singh, Rana P.; Agarwal, Rajesh (Current Cancer Drug Targets, 2004)
Several epigenetic alterations leading to constitutively active mitogenic and cell-survival signaling, and loss of apoptotic response are causally involved in self-sufficiency of prostate cancer (PCA) cells toward uncontrolled growth, and increased secretion of pro-angiogenic factors. Therefore, one targeted approach for PCA prevention, growth control and / or treatment could be inhibition of epigenetic molecular events involved in PCA growth, progression and angiogenesis. In this regard, silibinin / silymarin (silibinin is the major active compound in silymarin) has shown promising efficacy. Our extensive studies with silibinin / silymarin and PCA cells have shown the pleiotropic anticancer effects leading to cell growth inhibition in culture and nude mice. The underlying mechanisms of silibinin / silymarin efficacy against PCA involve alteration in cell cycle progression, and inhibition of mitogenic and cell survival signaling, such as epidermal growth factor receptor, insulin-like growth factor receptor type I and nuclear factor kappa B signaling. Silibinin also synergizes the therapeutic effects of doxorubicin in PCA cells, making it a strong candidate for combination chemotherapy. Silibinin / silymarin also inhibits the secretion of proangiogenic factors from tumor cells, and causes growth inhibition and apoptotic death of endothelial cells accompanied by disruption of capillary tube formation on Matrigel. More importantly, silibinin inhibits the growth of in vivo advanced human prostate tumor xenograft in nude mice. Recently, due to its non-toxic and mechanismbased strong preventive / therapeutic efficacy, silibinin has entered in phase I clinical trial in prostate cancer patients.
Keywords: endothelial